2007
DOI: 10.1021/nl063031m
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Rod Bioconjugates as Targeted Probes for Confocal and Two-Photon Fluorescence Imaging of Cancer Cells

Abstract: Live cell imaging using CdSe/CdS/ZnS quantum rods (QRs) as targeted optical probes is reported. The QRs, synthesized in organic media using a binary surfactant mixture, were dispersed in aqueous media using mercaptoundecanoic acid (MUA) and lysine. Transferrin (Tf) was linked to the QRs to produce QR-Tf bioconjugates that were used for targeted in vitro delivery to a human cancer cell line. Confocal and two-photon imaging were used to confirm receptor-mediated uptake of QR-Tf conjugates into the HeLa cells, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
152
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(152 citation statements)
references
References 28 publications
0
152
0
Order By: Relevance
“…[20][21][22][23] The increasing importance in measuring PL of anisotropic emitters like dye-biomolecule conjugates and luminescent nanomaterials with e.g., a shapeinduced anisotropy encouraged us to study polarization-induced changes of the detection efficiency of a commercial fluorometer and to quantify polarizationrelated uncertainties of PL measurements. For this purpose, we chose quantum dot-rods (QDRs), a novel class of semiconductor nanocrystals increasingly used as reporters for bioanalytical applications and medical diagnostics [28][29][30] and active materials for plasma displays, which consist of a spherical core and an elongated shell. QDRs possess unique photophysical properties, such as size-tunable absorption and emission spectra (dependent on the core diameter), huge absorption cross-sections, and narrow, symmetric emission bands like spherical quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] The increasing importance in measuring PL of anisotropic emitters like dye-biomolecule conjugates and luminescent nanomaterials with e.g., a shapeinduced anisotropy encouraged us to study polarization-induced changes of the detection efficiency of a commercial fluorometer and to quantify polarizationrelated uncertainties of PL measurements. For this purpose, we chose quantum dot-rods (QDRs), a novel class of semiconductor nanocrystals increasingly used as reporters for bioanalytical applications and medical diagnostics [28][29][30] and active materials for plasma displays, which consist of a spherical core and an elongated shell. QDRs possess unique photophysical properties, such as size-tunable absorption and emission spectra (dependent on the core diameter), huge absorption cross-sections, and narrow, symmetric emission bands like spherical quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 99%
“…71 The high photostability of QDs emitting in the near-infrared spectral region facilitates the monitoring of this transport process in real-time via high-resolution optical imaging. 7,[72][73][74][75] Thus a QD/QR-based nanoplatform facilitates not only the delivery of an antiretroviral drug across the BBB via interaction with endogenous transferrin receptors on the BBB but also allows the real-time monitoring of this transendothelial migration process via optical imaging. We have demonstrated that antiretroviral drug-loaded nanoparticles can deliver effective therapeutics across the BBB and that our nanoformulation has great potential in the treatment of neuro-AIDS and other neurological disorders.…”
Section: Targeting Hiv-1 In the Brainmentioning
confidence: 99%
“…The use of nanotechnology for numerous biomedical applications has become an area of intense research over the last decade. [1][2][3][4][5][6][7][8][9][10] The potential advantages of using nanomedicine over conventional HIV therapies include the capacity to incorporate, encapsulate, or conjugate a variety of drugs to target specific cell populations and to offer tunable and site-specific drug release. [11][12][13][14][15][16][17][18][19][20] Table 1 outlines the different types of current nanotherapeutics in HIV and lists their advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of strategies to deliver QDs to the cells, namely, transfection [65], electroporation, microinjection, uptake into cells via both targeting [66], and passive pathways are common routes for cell labeling and imaging [67]. In many cases, a targeted approach (e.g.…”
Section: Cdte Quantum Dots For Targeted In Vitro and In Vivo Imagingmentioning
confidence: 99%